Drought Analyses of the Horné Požitavie Region (Slovakia) in the Period 1966–2013 - Jaroslav Vido; Paulína Nalevanková; Ján Valach; Zbyšek Šustek; Tsegaye Tadesse (Advances in Meteorology)
This study focuses on the characterization of historical drought occurrences in the Horné Požitavie region of Slovakia over the period 1966–2013 using Standardized Precipitation-Evapotranspiration Index (SPEI). Trend analyses were evaluated by the Mann–Kendall (MK) test as well as cumulative sum of rank difference (CRD) test. The results showed that drought occurs in the region regularly (recurrent climate feature), while the trend analysis indicated the trend toward more arid climatic conditions. However, CRD trend analyses showed that the subtrend changed direction toward less drier conditions in the late 1980s and early 1990s. Analyses of SPEI trends in individual months showed a decreasing trend of drought occurrences during the cold months of the year (i.e., October to March), while an increasing trend was indicated from April to August. The evaluation of the impact of drought on agricultural production based on the oilseed rape yield indicated that drought represents a significant natural risk for the agrarian sector of the region. In addition, August value of the SPEI for six months was evaluated as a good indicator of drought impacts on agriculture. The trend analyses revealed no significant increase of drought impacts on agricultural production within the studied period.